STRATEGI PEMASARAN HOME INDUSTRY BATIK TULIS SUMBERSARI MAESAN BONDOWOSO - Devie Sonia Arini; Joko Widodo (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
This research is a qualitative descriptive study aimed to describe the marketing strategy of home industry of Batik Sumbersari at Maesan Bondowoso. The determining location method was purposive area, whereas the subject is the owner of Batik Sumbersari Maesan Bondowoso, and the data collection method was interviews, observation, and documents. Then the obtained data tested its validity through triangulation techniques. Based on the research results, Batik Sumbersari Maesan Bondowoso able to expand its business using the application of STP strategy (segmentation, targeting, positioning) rightly, and the creativity and professionalism make its products exclusive, elegant and luxury with its market segment is a burgeoning middle class constituted by social high class. Obviously, the consumers is an adults who have incomes more than enough. The target has been achieved not only within the domestic area but also at the foreign countries. Batik Sumbersari perform positioning by placing themselves as superior batik at the consumers’ mind by always maintain the quality of its batik tulis products which supported by a great concept  “one product one design one color” that makes Batik Sumbersari Maesan Bondowoso growing abroad.